Frequency squares of orders 7 and 8 - Krčadinac, Vedran (Utilitas Mathematica, 2007)
We enumerate frequency squares of orders 7 and 8 and the corresponding isotopism classes. An error in a previous paper by L.J. Brant and G.L. Mullen is discovered and partially corrected.